Remote access endoscopic parathyroidectomy: a study of 17 cases from Central India - Gajbhiye, Raj Narendra; Deshpande, Gayatri Amit; Tirpude, Bhupesh; Bhanarkar, Hemant; Akulwar, Vikrant; Kodape, Girish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: It has been debated that "remote access endoscopic parathyroidectomy" requires extensive dissection, thereby, increasing the risk of complications. Hence, the aim of this study is to assess the feasibility and safety of remote access endoscopic parathyroidectomy via the unilateral axilla-breast approach (ABA) and transoral vestibular approach (TOEPVA). Method: The study includes 17 patients with primary hyperparathyroidism undergoing endoscopic parathyroidectomy from January 2016 to December 2020. Of these, 11 patients underwent parathyroidectomy via unilateral ABA and 6 had TOEPVA. Preoperatively, ultrasonography of neck, sestamibi scan and CT scan neck were done to localise the diseased gland. Post operatively, Serum calcium and parathyroid hormone levels were monitored. Results: The mean age of patients was 35.6±10.5 years. Except one, all the patients were females. The mean operative time of the unilateral ABA and TOEPVA group was 93.67±28.64 minutes and 138.6±31 minutes respectively. Except for three patients, in all the patients, the parathormone levels normalised. One patient had hungry bone syndrome postoperatively. The mean hospital stay of the unilateral ABA and TOEPVA group was 3±1.5 days and 4±3.09 days respectively. One patient had post-operative transient recurrent laryngeal nerve paresis. Seroma and surgical emphysema were seen in two patients each. Conclusions: Remote Access Endoscopic parathyroidectomy may be considered safe in treatment of parathyroid tumours. Precise preoperative localisation is mandatory. In addition to a magnified view and a better illumination, the potential advantages of endoscopic techniques are better cosmetic results, decreased hospital stay and better patient comfort.